Law and Society in the South : a History of North Carolina Court Cases. - Wertheimer, John W. (New directions in southern history., 2015)
Law and Society in the South reconstructs eight pivotal legal disputes heard in North Carolina courts between the 1830s and the 1970s. Each case offers a vivid portrait of the laws, litigants, lawyers, judges, and affected communities, providing a better understanding of not only the Tar Heel State but also the South as a whole. This book examines some of the most controversial issues of southern history, including white supremacy and racial topics, the teaching of evolution in public schools, the role of religion in society, and Prohibition. Law and Society in the South divulges the true nat.